Pengaruh Kegiatan Bermain Terhadap Perkembangan Anak Usia Dini - Monica, Bunga; Andani, Fidhia; Suci Rahmadhani, Putri; Susejati; Salsabilla, Aulia; Lavenia, Oni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early childhood is a golden age period characterized by rapid growth and development. During this stage, children require appropriate stimulation to support their cognitive, social, emotional, language, and motor development. One form of stimulation that aligns with the characteristics of early childhood is play activity. This article aims to examine the influence of play activities on early childhood development and the role of parents and educators in supporting play-based activities. The method used in this study is a literature review by analyzing various research findings and relevant literature on play activities in early childhood. The findings indicate that play activities have a positive impact on children's cognitive, social, emotional, language, and motor development. Furthermore, the involvement of parents and educators in providing a safe, comfortable, and educational play environment is an important factor in maximizing the benefits of play for children. Therefore, play activities should be considered an essential part of early childhood education and parenting practices to support optimal child development.